E-Reputation in digital public spheres: Discourse network analysis of Indonesian Universities online - Dipa, Adzkia Kirana; Puspitasari, Lilis; Tripathi, Sangeeta (PRofesi Humas, 2026)
Background: E-reputation is increasingly important for the positioning of Indonesian universities in a complex landscape. The complex interplay among universities, media, and other actors in the construction of e-reputation, especially through the lens of actors’ networks and interactions, remains a rather understudied phenomenon. Purpose: The purpose of the research paper is to examine the relational positioning of Indonesia’s ten leading universities as depicted in the online media of 2024, thereby filling a gap in the understanding of the mechanisms of the construction of e-reputation. Methods: 279 online news articles related to top universities in Indonesia, such as Universitas Indonesia, UGM, ITB, etc., were analyzed through the application of Discourse Network Analysis (DNA 3.0.11), and then visualization was carried out through Visone 2.28.1. Network metrics were used to assess each university’s visibility. Result: The results show significant differences in centrality and media attention. Universitas Indonesia, UGM, and ITB are found to be the central institutions that play a crucial role as a hub during significant academic and policy events. On the other hand, other institutions are found to be peripheral. The attention from media sources such as Kompas.com and Republika.co.id centres on controversies surrounding achievements, in which students, alumni, and government actors play significant roles. Conclusion: E-reputation is not only a product of discourse networks among various actors, such as institutions and media, but also of media framing and stakeholder engagement. Implications: From this research, universities must consider how to manage their e-reputation by strategically engaging with media and stakeholders. Similarly, policymakers must consider how to incorporate e-reputation into policy and media literacy for the maintenance of reputation.